2022
DOI: 10.1038/s41467-022-33465-9
|View full text |Cite
|
Sign up to set email alerts
|

TFEB regulates sulfur amino acid and coenzyme A metabolism to support hepatic metabolic adaptation and redox homeostasis

Abstract: Fatty liver is a highly heterogenous condition driven by various pathogenic factors in addition to the severity of steatosis. Protein insufficiency has been causally linked to fatty liver with incompletely defined mechanisms. Here we report that fatty liver is a sulfur amino acid insufficient state that promotes metabolic inflexibility via limiting coenzyme A availability. We demonstrate that the nutrient-sensing transcriptional factor EB synergistically stimulates lysosome proteolysis and methionine adenosylt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 62 publications
0
5
0
Order By: Relevance
“…6 a, b and c) were in agreement with the above results that PD-1 restrained the Cm4 activation. The enrichments of metabolic pathways related regulons including Tfeb (24 g) [ 61 ] and Usf1 (20 g) [ 62 ] in PD-1 KO Cm4 cells were compatible with PD-1 regulating the metabolism in Cm4 cells.
Fig.
…”
Section: Resultsmentioning
confidence: 89%
“…6 a, b and c) were in agreement with the above results that PD-1 restrained the Cm4 activation. The enrichments of metabolic pathways related regulons including Tfeb (24 g) [ 61 ] and Usf1 (20 g) [ 62 ] in PD-1 KO Cm4 cells were compatible with PD-1 regulating the metabolism in Cm4 cells.
Fig.
…”
Section: Resultsmentioning
confidence: 89%
“…Furthermore, bile acid-induced FGF15/ 19 activates mTORC1 to phosphorylate and inhibit TFEB via a negative feedback loop. Further study suggests that in response to starvation TFEB activation also helps maintain cellular amino acid pool via activation of autophagy-lysosome proteolysis and the methionine cycle-transsulfuration pathway [37]. Taken together, new studies have revealed intriguing and complex crosstalk between bile acid metabolism and the autophagy-lysosome pathway in hepatocytes.…”
Section: Bile Acid Signaling Crosstalk With the Autophagy-lysosome Pa...mentioning
confidence: 92%
“…While cysteine and the disulfide form cystine are relatively insoluble and toxic at high concentrations [ 80 ], cysteine is a crucial OSC and intermediate in the synthesis of proteins [ 81 ], coenzyme A [ [82] , [83] , [84] , [85] , [86] ], taurine [ [87] , [88] , [89] , [90] ], iron-sulfur clusters [ [91] , [92] , [93] ], zinc-finger complexes/metalloproteins [ 94 , 95 ], and glutathione (GSH or γ-glutamyl-cysteinyl-glycine) [ 71 , 77 , 78 , 80 , 92 , [96] , [97] , [98] , [99] , [100] , [101] , [102] ]. Intracellular cysteine is maintained in the 80–100 μM range in most tissues except in the kidney, where its concentration is only ∼1 mM [ 58 ].…”
Section: Organic Sulfur Compounds – Cysteine To Glutathione (Gsh) Coe...mentioning
confidence: 99%
“…In the mitochondria, cysteine can be oxidized to hypotaurine and taurine [ 81 , 103 , 104 ], used by cysteine desulfurase (NFS1) to generate iron–sulfur (Fe–S) clusters [ [91] , [92] , [93] ], or function in sulfhydration and persulfidation reactions [ 22 , 23 , 30 , 105 ]. In the cytosol under conditions of abundant ATP concentrations and pantothenate (B5), cysteine is combined with B5 through a series of reactions that utilize three ATP molecules to form coenzyme A [ [82] , [83] , [84] , [85] , [86] ] ( Fig. 2 ).…”
Section: Organic Sulfur Compounds – Cysteine To Glutathione (Gsh) Coe...mentioning
confidence: 99%